DESAIN CATALOG SUPPLEMENT DAN GYM TUTORIAL DALAM MEDIA CETAK - CHANDRA ARDINATA, Drs. Ariusmedi, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Supplements in the thinking of ordinary people regarded as a dangerous drug and is not consumed in the long term by the human body, but actually supplements are supporting or auxiliary fitness in their daily activities and exercise on the human body.Supplement can be used for media promotion in gym, but not all people know if supplement safe for consumed in the long term by the human body becaue less-information from media promotion how to use suppplement for body, certainly has related with sport or gym and based on there instructure.To make easy consumed to know information about gym and supplement, then the researcher has design tutorial catalog supplement and gym.Method of collecting data, the researcher need some process to start design tutorial catalog supplemenet and gym, there are two design, such as 1) main data (primer) are visual data with types and kinds of technique gym. 2) additional data (sekunder) are theory based on, books, internet and sources. Data analysa is used anlysa SWOT. This method need for stengthen and complete deseign of tutorial catalog supplement and gym.Result of design is catalog has size A4 and show model of fitnes with some various and types of supplement. Media support from tutorial catalog and gym are x-banner, poster, pin, sticker, t-shirt, calender and brocur. The researcher hope promotion of tutorial catalog and gym with catalog media can succsesful and can change negative perception about supplement.Key word: Catalog, Supplements, Gym, Fitness, Tutorial.